Microfluidic paper-based analytical device (μPAD) for rapid detection of iron in agricultural soil - Marzuki, Nur Fatin Najihah (2020)
Accumulation of heavy metal in the environment becomes a health hazard because of their persistence, bioaccumulation and toxicity to plants, animals and human beings. Paper is increasingly accredited as a user-friendly and prevalent substrate for construction of microfluidic devices. Microfluidic paper-based analytical devices (μPADs) provide a substitute technology for development of economical, movable, disposable and low-cost diagnostic tools for improving point of care tests (POCTs). Hence, this microfluidic paper-based analytical devices (μpads) for rapid detection of iron metal in agricultural soil has reported LOD and LOQ as low as 5 ppm and 15 ppm for μpads analysis and 0.2 ppm and 0.6 ppm for UV/Visible spectroscopy. Calibration curve with linear range of 0.5 to 8 ppm for μpad and UV/Visible spectroscopy obtained